Optimal choice of vibration transducer - Мигущенко, Руслан Павлович; Кропачек, Ольга Юрьевна; Печерица, Тамара Валерьевна (Eastern-European Journal of Enterprise Technologies, 2011)
Considered the best choice vibration sensors. Defined the technical basis of vibration sensors, developed parametric and criterial bases, conducted a valuation indicators, carried out selection of the optimal solution on the basis of decision criteria